Study of the determinants of chronic malnutrition in northern Nigeria: Qualitative evidence from Kebbi and Bauchi states - Benson, Todd; Amare, Mulubrhan; Oyeyemi, Motunrayo; Fadare, Olusegun (International Food Policy Research Institute, 2017)
The burden in northern Nigeria of chronic malnutrition, particularly undernutrition, is among the heaviest globally. Close to half of all under-fives in the Northeast and Northwest geopolitical zones were estimated to be stunted in their growth for their age in 2013, compared to 22 percent in the rest of Nigeria. To inform discussions on future programming to address drivers of undernutrition, a rapid scoping study of chronic malnutrition in northern Nigeria was conducted. This report presents findings drawn from interviews with key informants and focus group discussions in Kebbi and Bauchi states and in Abuja conducted in April and May 2017.